PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOKSTORY UNTUK MENANAMKAN KARAKTER CINTA DAMAI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS III SD NEGERI 1 CILAJA - Intania Putri; Nana Sutarna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The character of peace-loving needs to be instilled through Pancasila Education. However, in today's digital era, there is a need for attractive technology-based learning media so that students are interested in participating in learning and can use the media anywhere. The facilities at SD Negeri 1 Cilaja are adequate, such as Chromebooks, projectors, speakers, and smart TVs, but their use in Pancasila Education is still limited. These technological facilities have not been optimally utilized to produce interactive and innovative learning media. In line with technological developments, E-bookstory can be used to enhance educators' creativity in producing engaging content. The objective of this study is to develop E-bookstory learning media and assess the feasibility and effectiveness of Pancasila Education learning media using E-bookstory on the topic of ethnic diversity. The research method used in this study is Research and Development (R&D). Data collection methods include observation sheets, interviews, expert validation, and student responses. Based on the feasibility test, the e-bookstory learning media for Pancasila Education, according to media experts, meets the feasible category with an average of 95%, and according to subject matter experts, it meets the highly feasible category with an average of 86%. Keywords: E-bookstory, Peaceful Love Character, Learning Media